The Role of Firm Value Disclosure - Rina Mukti Rahayu; Aprih Santoso (Information Technology and Science (ITScience), 2022)
The firm value is a reflection of every financial management action and decision that affects the stock market Price. CSR is suspected to be a control over company value considering that it can strengthen or weaken the effect of GCG and profitability ratios on firm value. This study aims analyze CSR in partially moderating the effect of GCG and profitability on firm value, and the partial influence of GCG and profitability on firm value. The data is taken from the financial statements and annual reports of manufacturing companies listed on the IDX for the period 2015 – 2021. Using purposive sampling, 21 companies are the samples of the study. The data was processed by multiple regression analysis using the help of the IBM SPSS Statistics 26 application. The results showed that GCG and profitability had a positive and significant effect on firm value. The results of testing the moderating variable showed that CSR moderated the effect of GCG and profitability on firm value.